Analisis Biaya Produksi dan Penerimaan Pendapatan Usaha Jamur Tiram Di Kabupaten Tuban - Hariyanti Hariyanti; Pebriyantiningsih Pebriyantiningsih (AKUNTANSI 45, 2023)
This study aims to describe and explain the production costs and business income obtained from several oyster mushroom cultivators in Tuban Regency. The samples in this study were 4 home oyster mushroom cultivators. The research method used in this research is descriptive qualitative, which is a method that aims to explain existing phenomena by observing, understanding, and applying the theory used. Based on the data analysis carried out, it can be seen that 4 samples of oyster mushroom cultivators in Tuban Regency for 4 consecutive years from 2016, 2017, 2018 and 2019 analysis of the production cost of Azza Mushrooms amounted to Rp. 3,325,000, -, from the mushroom village of Rp. 2,989,000, - from the mushroom house for Rp. 1,964,000, - and from the blessing mushroom house for Rp. 2,535,000. For analysis of revenue receipts of business. It can be concluded that there is only instability between one cultivation and another.